Islam and Dhimmitude: Where Civilizations Collide by Bat Ye’or; tr. Miriam Kochan and David Littman (Cranbury, NJ: Associated University Presses, 2002. 528 pages.) (American Journal of Islam and Society, 2004)
Islam and Dhimmitude is an attempt to confute the concept of “protectedminority” (under which Islamic civilization established what was, up to itstime, the most successful model of pluralistic society) with the worst aberrationsfrom that model. The subtitle “Where Civilizations Collide” indicateshow the author expects her polemic to serve the current wave of neoimperialism.The book seeks to recruit Christians in support of the Zionistproject by explaining away Christian expressions of appreciation ofMuslim tolerance as a false consciousness inspired by a self-hatred she calls dhimmitude, meaning a state of mind that acquiesces, even promotes,the victim’s own subjugation.The book’s first half is devoted to proposing a paradigm in whichQur’anic verses in favor of human rights are ignored, official acts to thebenefit of dhimmis are brushed off as machinations to breed resentmentbetween dhimmi groups, and injustices against Muslims are figments of theimagination invented to whitewash the Islamic master plan for subjugatingthe non-Islamic world into a state of dhimmitude. The second half workswithin this paradigm to vilify Christian anti-Zionists (including Europeansas well as Arabs) as dhimmi pawns of Muslim oppressors. (Curiously, shedoes not attempt to dismiss Jewish critics of Israel in the same manner.) ...